MANAJEMEN KONFLIK RUMAH TANGGA PERSPEKTIF HELMI BASRI - Azzahro, Najiya; Irsan (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
This study aims to examine conflict resolution in marriage, both before conflicts arise and when they occur, from the perspective of Helmi Basri. This research employs a descriptive qualitative method, with data sources consisting of recorded lectures delivered by Helmi Basri in programs organized by Islamic Family Solution, as well as relevant books and academic journals related to family conflict studies. The findings indicate that family conflict management consists of two stages: prevention before conflict occurs and resolution when conflict takes place. Conflict prevention is carried out by building a marital life based on piety to Allah, enhancing understanding of the rights and obligations of husband and wife, maintaining communication and family closeness, fostering mutual acceptance of each other’s shortcomings, and cultivating an attitude of qana’ah (contentment). Meanwhile, conflict resolution during disputes is implemented by reminding one another of the spouse’s virtues, addressing problems wisely without being driven by emotion, improving the quality of worship and increasing supplication, and striving to adapt to the situations faced. This study is expected to contribute to the development of Islamic family studies, particularly in relation to strategies for preventing and resolving marital conflicts, in order to realize a harmonious family characterized by sakinah, mawaddah, and rahmah.